Literature Study: Primary Immunodeficiency - Rahmadinna, Sandia Anggun; Yuar, Alana Akmal; Musyafa, Aulia Putri; Hardiant, Excell Defry; Putri, Baiq Ghefira Rojwani; Muliana, Atriska Citra; Salsabila, Septy Rianty Putri; Ningrum, Sania Tresna; Narendra, Ahmad Wahyu; Ramadhania, Yasmine Najla; Habib, Philip (Jurnal Biologi Tropis, 2025)
Abnormalities in immune system development and function result in increased susceptibility to infection and reactivation of latent infections. Other immunodeficiencies can result in mild infections and may first be detected in adulthood. This literature review aims to discuss primary immunodeficiencies, including their definition, causes, treatment, and examples of the diseases they cause. This literature review was compiled through a literature search method by reviewing various scientific journals obtained from databases such as PubMed, Google Scholar, and ScienceDirect. The results Primary immunodeficiency disease (PID) results from immune system defects caused by mutations in the genetic code that codes for components of the body's immune system. PID is broadly classified as either a disorder of adaptive immunity (T-cell, B-cell, or combined immune deficiencies) or innate immunity (phagocyte and complement deficiencies). Patients with PID may experience a variety of lung problems, including recurrent lower respiratory tract infections, lung parenchymal abnormalities, asthma, ventilation abnormalities, and bronchiectasis (BE). In conclusion, primary immunodeficiency disease (PID) refers to a large, heterogeneous group of disorders characterized by abnormalities in the development and/or function of the immune system. These conditions result from immune system defects caused by mutations in the genetic code that codes for components of the body's immune system.